Sexual behaviour of married men during pregnancy and after childbirth in Ibadan: Evidence from focus group discussions (2005)
Male role and responsibility in reproductive health matters become consistent prerequisites to understanding maternal issues generally. Through focus group discussions (FGDs}; this exploratory research investigates sexual behaviour of married men during pregnancy and afterbirth in Ibadan Southwestern Nigeria as a way of highlighting the links between these periods and pregnancy outcomes and the health status of couples. The study shows that sexual behaviour of men is influenced by the interplay of religious, socio-cultural and ideological factors. The specific results include that: men engage in coitus with their pregnant wives with the upper limit of 4 months among the Hausa;: postpartum sexual abstinence varies in duration with an average of 40 days across cultural settings; one sixth of the respondents agreed engaging in sexual intercourse with other women in order to- reduce their wives' vulnerability to the risks associated with pregnancy; and while men often use condom to prevent sexually transmitted infections (STIs) from women other than their wives, most married men with established or presumed cases of STIs appear to be relatively casual and undiplomatic in handling this issue. These findings suggest that programmes targeted at husbands and their reproductive health orientation appear necessary to reduce the frequency of STIs and other negative reproductive health outcomes among couples.